Using authentic audio-visual materials english language listening test - Ab. Ghani, Mohd. Khairull (2013)
This study aimed to extend the findings of previous studies on visually supported listening. To fulfill this purpose, 30 Diploma in Medical Laboratory students were selected from University College Shahputra located in Kuantan Pahang. These students were chosen through convenience sampling and divided into two groups (Group A and Group B). Both groups have the same proficiency level. Both groups took audio-only listening test and audio-visual listening test respectively. Both tests had been conducted early in the semester. Group A had taken audio-only listening test first and group B had taken audio-visual listening test first. This study looked into the effects of using Authentic Audio-visual Materials in English Language Listening Test. The study also investigated student’s perceptions regarding the use of visuals in English listening test. Through the use of tests and questionnaire, the study determined whether the use of visuals benefited students in their listening performance. Findings indicated that there were slight significant differences for listening performance for group A participants in audio-visual listening test. However, group B participants did not perform well in audio-visual listening test. It shows that the audio-only listening test needs to be taken first in order for the students to be able to perform well in audio-visual listening test. Analyses of student’s perceptions revealed that group A participants felt that audio-visual listening is beneficial to them. However, group B participants felt that audio-visual listening test did not help them to perform well.